OCEANS 2007 - Europe 2007
DOI: 10.1109/oceanse.2007.4302224
|View full text |Cite
|
Sign up to set email alerts
|

The Qualitative and Quantitative Distribution in Phytoplankton and Zooplankton of Southern Black Sea of Cape Sinop, Turkey in 1999-2000

Abstract: In the present study, seasonality and composition of phytoplankton and zooplankton were comparatively studied at two stations (one inshore and one offshore) off Sinop, in southern Black A total 76 genera including 149 species and varieties were identified, of which 46% were dinoflagellates and 34% were diatoms in phytoplankton. Abundance of the genera Emiliana (in January-May 1999), Pseudosolenia and Ceratium (in MarchOctober 2000) were higher than that of the other genera in almost every sampling period. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Most fecundity studies have been of Calanus euxinus Hulsemann, 1991 in the northern Black Sea (Greze and Baldina, 1967;Sazhina, 1996;Arashkevich et al, 1998;Ostrovskaya et al, 1998;Besiktepe and Telli, 2004). To fill this research gap, we seek to determine the egg production rate of A. clausi and found among the area's plankton population throughout the year (Ünal, 2002;Üstün, 2005;Bat et al, 2007;. No such study has heretofore been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Most fecundity studies have been of Calanus euxinus Hulsemann, 1991 in the northern Black Sea (Greze and Baldina, 1967;Sazhina, 1996;Arashkevich et al, 1998;Ostrovskaya et al, 1998;Besiktepe and Telli, 2004). To fill this research gap, we seek to determine the egg production rate of A. clausi and found among the area's plankton population throughout the year (Ünal, 2002;Üstün, 2005;Bat et al, 2007;. No such study has heretofore been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been only focused on lakes, rivers and the sea. There are a few studies on estuarine zooplankton in Turkey (Bat et al, 2007, Işinibilir et al, 2008. This study might contribute to Turkish zooplankton fauna and be a reference for detailed studies in future on Kö-prüçay estuary zone and other estuaries.…”
Section: Resultsmentioning
confidence: 99%
“…It was recorded that the most important peaks were observed in winter and autumn months off Sinop in the years 1999-2000 [14,19]. Yıldız ve Feyzioğlu [24] Seasonal distribution of mesozooplankton (excluding Noctiluca scintillans) abundance and biomass values showed no statistical differences (P > 0.05) among years although higher mean values observed in 2003, followed by 2004 (37,400±10,400 ind.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, in the current study the changes (yearly interval scales) in the distribution of the zooplankton composition were presented for the period of 2002-2004. The first zooplankton studies on the Turkish coasts of Black Sea started with the identification of plankton species on the shores of Trabzon between 1952 and 1953 [5]. Subsequently, the number of these studies rapidly increased in southern Black Sea [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. It is observed that studies carried out on plankton are predominantly based on discrete samples belonging to certain time periods.…”
Section: Introductionmentioning
confidence: 99%